Stereoselective Conversions of Carbohydrate Anomeric Hydroxyl Group in Basic and Neutral Conditions - Monika Khaleri; Qingjiang Li (Molecules, 2024)
The rapidly growing glycoscience has boosted the research on the synthesis of glycans and their conjugates, which are centered on the stereoselective formation of glycosidic bonds. Compared to the mainstream acid-promoted glycosylation method that undergoes the SN1 type mechanism, the basic/neutral conditions give better stereo control via the SN2 mechanism. Anomeric hydroxyl group transformation, whether to form glycosidic bonds directly or to install a leaving group for later glycosylation, is key to carbohydrate synthesis, and the strategies in the stereo control of these reactions under basic/neutral conditions are summarized in this review. Different stereo control strategies that are applicable to protected or unprotected hemiacetals are discussed, and case-by-case studies of literature reports in the past two decades are included. In addition to surveying literature reports, this review aims at providing insights into the strategic considerations in the development of a stereoselective method for the formation of glycosidic bonds.